Metabolic syndrome criteria and its association with type 2 diabetes and cardiovascular diseases - Yadav, Dhananjay; Puranik, Nidhi; Sen, Amit; Mishra, Meerambika; Kwak, Minseok; Jin, Jun-O (Progress in Nutrition, 2020)
Metabolic syndrome is a cluster of metabolic anomalies such as insulin resistance, obesity, abdominalfat deposition, hypertension and dyslipidemia, which put an individual at a higher risk of developingcardiovascular complications. Global variation in ethnicity, culinary habits, availability of nutritious elements,lifestyle, economic status and disease tolerance/susceptibility of the workforce is reflected in the definitionof the syndrome given by various public health entities. The present review summarizes the recent advancesin the understanding of metabolic syndrome which has been discussed at length by different organizations.A greater insight into diagnostic criteria of metabolic syndrome will improve our understanding and moreimportantly enable the prevention and management of this complex condition.